P114 What Skills, Experience And Training Are Need To Work In Integrated Respiratory Specialist Roles And How Can We Roll These Posts Out In The Uk?. (10th November 2014) - Roberts, NJ; Ward, M; Patel, IS; Yorke, J; Williams, J; Walters, R; McKevitt, M; Edwards, S
Abstract : Aims: There is an increased drive towards healthcare integration in the UK (UK) to adapt to new health care needs. In response to this, new ways of delivering care have been developed such as the provision of integrated respiratory specialists. This project set out to describe these roles, the key skills needed and how junior staff can aspire to these roles. Methods: Semi-structured telephone interviews with 12 integrated care specialists or those currently working with integrated respiratory care teams were undertaken to explore and discuss the role of integrated respiratory specialists. Results: Nine integrated specialists were interviewed (6 physicians, 2 nurses, 1 physiotherapist). One Specialist Trainee (StR), a general practitioner (GP) and a pharmacist were also interviewed. The integrated role was variable for participants; most were involved in MDTs, education for staff and developing guidance, with some involved in community or virtual clinics. Physicians were more likely to be involved in Acute Medical Unit reviews. Five interviewees had two joint leads with either two physicians, or a physician and a nurse. Key skills identified by the interviewees included respiratory specialist knowledge, prior primary care experience as well as knowledge of the NHS, commissioning and social services processes. Specific training included conflict management, advanced communication and research and evaluation skills (health economics and service evaluation). Three areas were highlighted to support the establishment of new posts: clear details about the posts and standards of care; embedding integrated care into training; increasing visibility of this new area and gaining support from appropriate organisations. Conclusions: Interviewees highlighted that existing posts should be used as exemplars to provide junior staff with more information about these roles. Greater collaboration with professional societies such as the BTS, ERS and PCRS for education as well as to promote and advance these new potential career pathways should be undertaken. Funded by the British Thoracic Society.